Proceedings - Natural Language Processing in a Deep Learning World 2019
DOI: 10.26615/978-954-452-056-4_082
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Polarity Detection in Azerbaijani Social News Articles

Abstract: Text classification field of natural language processing has been experiencing remarkable growth in recent years. Especially, sentiment analysis has received a considerable attention from both industry and research community. However, only a few research examples exist for Azerbaijani language. The main objective of this research is to apply various machine learning algorithms for determining the sentiment of news articles in Azerbaijani language. Approximately, 30.000 social news articles have been collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Almost the entire NLP pipeline for Turkish exists in a toolkit, called TurkishDelightNLP (Alecakir et al, 2022). Text classification studies can also be observed for Turkish and Azerbaijani languages e.g., sentiment of social news articles in Azerbaijani (Mammadli et al, 2019), tweet topic classification (Yüksel et al, 2019) and sentiment analysis (Mutlu and Özgür, 2022) in Turkish. (ii) Cross/multi-lingual models: this track of research includes efforts on aligning monolingual embedding spaces of various Turkic languages, which are often affected by low-resource constraints (Kuriyozov et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Almost the entire NLP pipeline for Turkish exists in a toolkit, called TurkishDelightNLP (Alecakir et al, 2022). Text classification studies can also be observed for Turkish and Azerbaijani languages e.g., sentiment of social news articles in Azerbaijani (Mammadli et al, 2019), tweet topic classification (Yüksel et al, 2019) and sentiment analysis (Mutlu and Özgür, 2022) in Turkish. (ii) Cross/multi-lingual models: this track of research includes efforts on aligning monolingual embedding spaces of various Turkic languages, which are often affected by low-resource constraints (Kuriyozov et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Although there are few researches in the field of text classification in Azerbaijani language, one of the research projects shows that it is possible to achieve excellent result in this field. The research [7] aimed to determine the sentiment of news articles in Azerbaijani language where researchers obtained 96.79% f1-score by using SVM classifier with TF-IDF vectorization technique. The results revealed that neglecting topic domain-defining terminology was more appropriate in the context of news opinion mining, and techniques that took this into account performed better.…”
Section: Literature Reviewmentioning
confidence: 99%